PENGARUH PENGGUNAAN BAHAN BAKAR PERTALITE DAN PERTAMAX TERHADAP PEFORMA MESIN PADA MOTOR EMPAT LANGKAH” - Aprinaldi Aprinaldi; Dori Yuvenda; Sri Rizki Putri Primandari; Randi Purnama Putra (Jurnal Vokasi Mekanika (VoMek), 2024)
Every year, the population continues to grow, leading to an increase in daily activities. To meet transportation needs, light motor vehicles, such as petrol motorcycles, are the main choice. Motorbikes have been widely marketed in various models. Along with the development of knowledge about motorbikes, there is a type of automatic motorbike (matic). internal combustion piston engine is a type of heat engine that transforms fuel energy into mechanical energy through the movement of a piston. It uses one or more moving pistons to convert pressure into rotational motion. Inside the engine cylinder, a fuel mixture is introduced, producing hot gases that push the piston down and drive the crankshaft. The types of fuel used include premium, pertalite, and pertamax. The combustion of these fuels has an impact on the environment. PT Pertamina (Persero) plans to discontinue premium fuel and replace it with pertalite and pertamax, which are increasingly favoured by consumers. A study revealed that pertamax fuel is more effective at improving engine performance than pertalite, as shown by dyno test results that showed the highest torque and power values with pertamax fuel at 6,000 RPM, namely 6.01 kW and 9.53 nM.